Two new species of Clavaria (Agaricales, Basidiomycota) from Central China - Yan, Jun; Wang, Xiao-Yan; Wang, Xiao-Hui; Chen, Zuo-Hong; Zhang, Ping (Phytotaxa, 2020)
Species of Clavaria (Clavariaceae, Agaricales) collected from China were studied using morphological and molecular methods. Two species, C. griseolilacina and C. sinensis were described as new species; both possess branched and pale purple-tinged fruit bodies. However, the former possess a few branched, while the latter is profusely branched. The phylogenetic analysis based on the internal transcribed spacer (ITS) sequences confirmed the distinctions between these two new species and their close relationships with C. rubicundula and C. fumosa in the genus. An evolutionary tendency in genus Clavaria was discussed. Additionally, morphological features of the two new species were described in detail and were illustrated with line drawings and photographs. Holotypes of the new species are deposited in the Mycological Herbarium of Hunan Normal University (MHHNU). The ITS sequences generated in this study were deposited in GenBank. A key is provided for the known Clavaria species in China.